The effect of protonation and oxidation state of polyaniline on the stability of gold nanoparticles. (September 2016) - Kabomo, T.M.; Scurrell, M.S.
Graphical abstract: Highlights: Mechanism of Au nanoparticles stabilized by PANI revealed. Effect of added reagents on PANI restructuring determined. Aggregation of Au nanoparticles occurs when reducing or oxidizing agents are added. The shape of the aggregates formed is dependent on the rate of agglomeration. Abstract: It has been shown that Au NPs are stabilized by PANI through (1) a charge transfer from the imine nitrogens on PANI to the AuNPs and (2) by H-bonding between PANI and unreduced AuCl4 − ions adsorbed on Au NPs. The addition of electrolytes such as NaCl or NaOH which do not cause structural changes to PANI that could affect either the charge transfer or the H-bonding did not cause any particle aggregation. Aggregation of Au NPs stabilized by PANI was only observed when solutions of NaBH4, HCl, and (NH4 )2 S2 O8 were added to dispersions of AuPANI. Sodium borohydride reduces PANI by transforming the imine groups on PANI to amine groups. In addition, NaBH4 reduces further the "unreduced" AuCl4 − ions that are adsorbed on AuNPs. This results in a reduction in the attractive forces between Au NPs and PANI. The addition of a solution of HCl to a suspension of PANI causes the formation of polysemiquinone cation radicals through the protonation of PANI. This leads to the reduction in the ability of PANI to form H-bonds. Similarly, the addition of (NH4 )2 S2 O8 to the AuPANI suspension oxidizes PANI by transforming amine groups to imine groups. However the polymer degrades through the hydrolysis of the imine group under high electrochemical potentials (E > 0.7 V). All these conditions lead to the aggregation of Au NPs. Chain-like aggregates (nanowires) form when agglomeration is induced by the reduction of PANI while close-packed aggregates form when PANI is oxidized or protonated.